LncRNA NBR2 Inhibits the Malignancy of Thyroid Cancer, Associated With Enhancing the AMPK Signaling - Yang, Wen; Zheng, Zhikun; Yi, Pengfei; Wang, Shi; Zhang, Ning; Ming, Jie; Tan, Jie; Guo, Hui (Frontiers in Oncology, 2020)
Long non-coding RNA NBR2 is a transcript of the Neighbor of BRCA1 gene 2 and can regulate tumor development. However, there is little information on the role of NBR2 in the progression of thyroid cancers (TC). Here, we show that NBR2 expression is down-regulated in TC tissues and associated with histologic subtypes of TC. NBR2 expression was variably reduced in different TC cells. While NBR2 silencing significantly inhibited the malignancy of BCPAP cells by decreasing cell proliferation, clonogenicity, wound healing and invasion as well as tumor growth in vivo, and increased spontaneous apoptosis NBR2 over-expression had opposite effects in BHT101 cells. In comparison with non-tumor thyroid epithelial Nty-ori 3-1 cells, obviously increased GLUT-1 expression, but decreased AMPK and ACC phosphorylation were detected in TC cells. While NBR2 silencing further enhanced GLUT-1 expression and reduced AMPK and ACC phosphorylation as well as the EMT process in BCPAP cells NBR2 over-expression also had opposite effects in BHT101 cells. Similar patterns of GLUT-1 expression and AMPK and ACC phosphorylation were detected in the different types of xenograft TC tumors in vivo. Therefore, such data indicated that NBR2 acted as a tumor suppressor of thyroid cancers by enhancing the AMPK signaling and NBR2 may be a potential biomarker and therapeutic target for thyroid cancers.